The prodromal phase of leucine‐rich repeat kinase 2–associated Parkinson disease: Clinical and imaging Studies. Issue 5 (28th March 2017) - Pont‐Sunyer, Claustre; Tolosa, Eduardo; Caspell‐Garcia, Chelsea; Coffey, Christopher; Alcalay, Roy N.; Chan, Piu; Duda, John E.; Facheris, Maurizio; Fernández‐Santiago, Rubén; Marek, Kenneth; Lomeña, Francisco; Marras, Connie; et al.
ABSTRACT: Background: Asymptomatic, nonmanifesting carriers of leucine‐rich repeat kinase 2 mutations are at increased risk of developing PD. Clinical and neuroimaging features may be associated with gene carriage and/or may demarcate individuals at greater risk for phenoconversion to PD. Objectives: To investigate clinical and dopamine transporter single‐photon emission computed tomography imaging characteristics of leucine‐rich repeat kinase 2 asymptomatic carriers. Methods: A total of 342 carriers' and 259 noncarriers' relatives of G2019S leucine‐rich repeat kinase 2/PD patients and 39 carriers' and 31 noncarriers' relatives of R1441G leucine‐rich repeat kinase 2/PD patients were evaluated. Motor and nonmotor symptoms were assessed using specific scales and questionnaires. Neuroimaging quantitative data were obtained in 81 carriers and compared with 41 noncarriers. Results: G2019S carriers scored higher in motor scores and had lower radioligand uptake compared to noncarriers, but no differences in nonmotor symptoms scores were observed. R1441G carriers scored higher in motor scores, had lower radioligand uptake, and had higher scores in depression, dysautonomia, and Rapid Eye Movements Sleep Behavior Disorder Screening Questionnaire scores, but had better cognition scores than noncarriers. Among G2019S carriers, a group with "mild motor signs" was identified, and was significantly older, with worse olfaction and lower radioligand uptake. Conclusions: G2019S and R1441G carriers differ from their noncarriers' relatives in higher motor scores and slightly lower radioligand uptake. Nonmotor symptoms were mild, and different nonmotor profiles were observed in G2019S carriers compared to R1441G carriers. A group of G2019S carriers with known prodromal features was identified. Longitudinal studies are required to determine whether such individuals are at short‐term risk of developing overt parkinsonism. © 2017 International Parkinson and Movement Disorder Society